Effect of Cetrimide with Bioceramic or Calcium Hydroxide Intracanal Medication - Pontes, Larissa Braz [UNESP]; Lopes, Camila Soares [UNESP]; Pradelli, Jéssica Arielli [UNESP]; Tanomaru-Filho, Mário [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Universidad de Costa Rica, 2025)
This study evaluated the pH, solubility, and intratubular decontamination of bioceramic intracanal medications Bio-C® Temp (BCT), a calcium hydroxide-based paste Calen® (CAL), and their associations with 1% Cetrimide (CTR): BCT, CAL, BCT/CTR, CAL/CTR. Polyethylene tubes filled with the medications were used for pH measurement at intervals of 1, 3, 7, 14, and 21 days. Solubility was evaluated after 14 days of immersion in distilled water at 37°C. Bovine dentin tubules contaminated with Enterococcus faecalis were used to assess intratubular decontamination using confocal laser scanning microscopy and Live/Dead BacLight Bacterial dye three days after exposure to the medications and a Control Group using Polyethylene glycol 400. Statistical analysis was performed using ANOVA and Tukey tests (p<0.05). CAL/CTR exhibited the highest pH after 1 day (p<0.05). CAL had the highest pH values at 14 and 21 days (p<0.05). BCT showed the lowest pH values at 3 days, and BCT/CTR at 7 and 21 days (p<0.05). The association of CTR did not affect the solubility of the medications (p > 0.05). CAL demonstrated superior intratubular decontamination (p<0.05), while CAL/CTR, BCT, and BCT/CTR showed similar results (p>0.05). The association of 1% cetrimide did not increase the intratubular decontamination of Bio-C® Temp and decreased the antibacterial activity of Calen®. The calcium hydroxide medication in a viscous vehicle exhibited higher alkaline potential, solubility, and intratubular decontamination. Este estudio evaluó el pH, la solubilidad y la descontaminación intratubular de las medicaciones intracanal biocerámicas Bio-C® Temp (BCT), una pasta a base de hidróxido de calcio Calen® (CAL) y sus combinaciones con Cetrimida al 1% (CTR): BCT, CAL, BCT/CTR, CAL/CTR. Se utilizaron tubos de polietileno llenos con las medicaciones para medir el pH a intervalos de 1, 3, 7, 14 y 21 días. La solubilidad se evaluó después de 14 días de inmersión en agua destilada a 37°C. Se utilizaron túbulos dentinarios bovinos contaminados con Enterococcus faecalis para evaluar la descontaminación intratubular mediante microscopía confocal de escaneo láser y el tinte bacteriano Live/Dead BacLight, tres días después de la exposición a las medicaciones y a un grupo de control utilizando polietilenglicol 400. El análisis estadístico se realizó mediante pruebas ANOVA y Tukey (p<0.05). CAL/CTR mostró el pH más alto después de 1 día (p<0.05). CAL tuvo los valores de pH más altos a los 14 y 21 días (p<0.05). BCT mostró los valores de pH más bajos a los 3 días, y BCT/CTR a los 7 y 21 días (p<0.05). La adición de CTR no afectó la solubilidad de las medicaciones (p>0.05). CAL demostró una descontaminación intratubular superior (p<0.05), mientras que CAL/CTR, BCT y BCT/CTR mostraron resultados similares (p>0.05). La inclusión de cetrimida al 1% no mejoró la descontaminación intratubular de Bio-C® Temp y redujo la actividad antibacteriana de Calen®. Calen® en un vehículo viscoso exhibió un mayor potencial alcalino, solubilidad y descontaminación intratubular.